Food for fuel: The effect of U.S. energy policy on Indian poverty - Ujjayant Chakravorty; Marie-Hélène Hubert; Beyza Ural Marchand (Center for Economic Studies and ifo Institute (CESifo), 2012)
Many countries have adopted energy policies that promote biofuels as a substitute for gasoline in transportation. For instance, 40% of U.S. grain is now used for energy and this share is expected to rise significantly under the current Renewable Fuels Mandate. This paper examines the distributional effects of the U.S. mandate on India. First, we use a model with endogenous land use to estimate the effect of biofuel policy on the world price of food commodities, in particular rice, wheat, sugar and meat and dairy, which provide almost 70% of Indian food calories. We obtain world price increases of the order of 10% for most of these commodities. Using Indian micro-level survey data for consumption and income, we carefully estimate the effect of these price increases on household welfare. We account for negative consumption impacts as well as the positive effects through wages and income. We consider both perfect and imperfect pass-through from world to domestic prices. We show that the net impact on welfare is negative as well as regressive, i.e., U.S. biofuels policy affects the poorest people the most. About 42 million new poor may be created in India alone. Under imperfect pass-through, this number declines to 16 million. The main implication is that U.S. energy policy that mandates the production of fuel from food may lead to a sharp increase in world poverty.
Keywords: D31; O12; Q24; Q42; 330; clean energy; food prices; household welfare; renewable fuel standards; poverty